Fall Treatment with Fumagillin Contributes to an Overwinter Shift in Vairimorpha Species Prevalence in Honey Bee Colonies in Western Canada - Sarah Biganski; Oleksii Obshta; Ivanna Kozii; Roman Koziy; Michael W. Zabrodski; Midhun S. Jose; Jenna M. Thebeau; Marina C. B. Silva; Muhammad F. Raza; Fatima Masood; Sarah C. Wood; Elemir Simko (Life, 2024)
(1) Background: Microsporidiosis (nosemosis) is an intestinal disorder of adult honey bees caused by the microsporidian pathogens Vairimorpha apis and Vairimorpha ceranae. In Canada, fumagillin is an approved antibiotic used to treat this disease. However, the recommended dosage is based on efficacy studies for V. apis, the native pathogen in European honey bees. Since the detection of V. ceranae in Apis mellifera, V. ceranae became more prevalent in managed European honey bees and seems to have replaced V. apis due to yet unknown reasons. (2) Methods: This colony study investigated the efficacy of fumagillin administered in the fall to colonies infected with both V. apis and V. ceranae and its effects on the Vairimorpha species’ prevalence overwinter. Spore loads in control and fumagillin-treated colonies were analysed by microscopy; Vairimorpha species prevalence was determined molecularly and infection and treatment effects on colony productivity were assessed. (3) Results: Fall fumagillin treatment was associated with a temporary reduction in spore load, but there was no difference in spore loads between treated and control colonies the following spring. Interestingly, fumagillin-treated colonies had a significantly greater prevalence of V. ceranae relative to V. apis the following spring, suggesting fumagillin is less effective in controlling V. ceranae.